Consumo Ambientalmente Consciente: os meus, os seus e os nossos interesses - Beck, Ceres Grehs (2010)
Understanding the relationship between the human being and the environment is a need present in the agenda of companies, governments, academy and consumers. Towards the sustainable development, everyone is looking for the causes and possible solutions to mitigate the environmental problems, since these might affect all of us. So, this study aimed to identify if the awareness of adverse consequences and the consumers' environmental concern contribute to the environmental conscious behaviors. These objectives were reached through the application of in-depth interviews allied with the projective technique with 33 consumers aged between 18 to 66 years old that were residents in João Pessoa city. The interpretation of the speeches through the content analysis with qualitative approach oriented by Bardin (1977) generated thematic categories and variables. These, when confronted in the light of the theoretical references, allowed the analysis of the environmental conscious behaviors and if these are oriented by selfish values (anthropocentric) or are guided by altruistic and biospheric values (ecocentric). The results showed a paradoxical consumers relationship that ranges among consuming less to preserve the environment and the planet (values oriented to our interests ) or consuming more to reach personal satisfaction in a way to maintain the own life quality, the health and the personal well-being ( my interests ). The study reveals a high concern and understanding referred to the negative consequences of the environmental degradation. However, despite of the declared intention of acting on behalf of the environment, the consumers demonstrate passivity and selfish behaviors. In this context, the consumers impute to the companies and the governments the environmental care and do not exercise their power to maintain the society s balance. From these verifications, it is necessary to make the consumers aware and to motivate them to change values and behaviors, towards this new thought related to an ecological rationality. The sustainable development can be reached by addressing the government actions together with the marketing strategies, but also counting with the consumer's active participation in this sense.